A Comprehensive Review of the Cardiovascular Protective Properties of Silibinin/Silymarin: A New Kid on the Block - Nikolaos P. E. Kadoglou; Chrystalla Panayiotou; Michail Vardas; Nikolaos Balaskas; Nikolaos G. Kostomitsopoulos; Alexandra K. Tsaroucha; Georgia Valsami (MDPI AG, 2022)
Silibinin/silymarin has been used in herbal medicine for thousands of years and it is well-known for its hepato-protective properties. The present comprehensive literature review aimed to critically summarize the pharmacological properties of silymarin extract and its main ingredient silibinin in relation to classical cardiovascular risk factors (e.g., diabetes mellitus, etc.). We also assessed their potential protective and/or therapeutic application in cardiovascular diseases (CVDs), based on experimental and clinical studies. Pre-clinical studies including in vitro tests or animal models have predominantly implicated the following effects of silymarin and its constituents: (1) antioxidant, (2) hypolipidemic, (3) hypoglycemic, (4) anti-hypertensive and (5) cardioprotective. On the other hand, a direct amelioration of atherosclerosis and endothelial dysfunction after silymarin administration seems weak based on scarce data. In clinical trials, the most important findings are improved (1) glycemic and (2) lipid profiles in patients with type 2 diabetes mellitus and/or hyperlipidemia, while (3) the anti-hypertensive effects of silibinin/silymarin seem very modest. Finally, the changes in clinical endpoints are not robust enough to draw a firm conclusion. There are significant limitations in clinical trial design, including the great variety in doses and cohorts, the underlying conditions, the small sample sizes, the short duration and the absence of pharmacokinetic/pharmacodynamic tests prior to study commitment. More data from well-designed and high-quality pre-clinical and clinical studies are required to firmly establish the clinical efficacy of silibinin/silymarin and its possible therapeutic application in cardiovascular diseases.